El poder político y su impacto en la independencia judicial en el Ecuador: Un estudio sobre los riesgos de la intervención en el sistema de justicia ecuatoriano. - Vinueza Abad, George Anthony (2025)
The research analyzed the influence of political power on judicial independence in Ecuador, focusing on how such interference compromises the impartiality and autonomy of judges. The study addressed the impact of political and economic pressures on the judicial system, affecting essential ethical principles such as independence, integrity, and impartiality in decision-making, particularly in highly politicized cases. Through a qualitative approach and data collection via surveys of judges, the main barriers to the exercise of independent justice were identified, including the appointment of magistrates based on political criteria and the lack of transparency in judicial processes. The results revealed that political interference is a constant threat to public confidence in the Ecuadorian judicial system, affecting the legitimacy of the decisions issued. Finally, recommendations were proposed to strengthen judicial independence by implementing mechanisms to limit political interference in the administration of justice, ensuring judicial impartiality, respect for due process, and the reinforcement of the rule of law.